2009
DOI: 10.1603/029.102.0617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative Planting Strategies to Reduce Wheat Stem Sawfly (Hymenoptera: Cephidae) Damage to Spring Wheat in the Northern Great Plains

Abstract: Wheat, Triticum aestivum L., producers are often reluctant to use solid-stemmed wheat cultivars resistant to wheat stem sawfly, Cephus cinctus Norton (Hymenoptera: Cephidae), due to concerns regarding yield, efficacy or market opportunities. We evaluated the impact of several planting strategies on wheat yield and quality and wheat stem sawfly infestation at two locations over a three-year period. Experimental units consisted of large plots (50 by 200 m) located on commercial farms adjacent to wheat stem sawfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Wheat stem sawfly oviposition behavior, as in other insects (Hattori, 1988;Nottingham, 1988), is a process involving different host location cues as well as host acceptance cues (Ramaswamy, 1988). Improvement of trap crop effectiveness is needed before this practice is widely adopted (Beres et al, 2009) and the results obtained in the present study indicate that the choice of trap cultivar can have an impact on WSS preference, leading to a concentration of feeding larvae in the trap. Improvement of trap crop effectiveness is needed before this practice is widely adopted (Beres et al, 2009) and the results obtained in the present study indicate that the choice of trap cultivar can have an impact on WSS preference, leading to a concentration of feeding larvae in the trap.…”
Section: Discussionmentioning
confidence: 73%
“…Wheat stem sawfly oviposition behavior, as in other insects (Hattori, 1988;Nottingham, 1988), is a process involving different host location cues as well as host acceptance cues (Ramaswamy, 1988). Improvement of trap crop effectiveness is needed before this practice is widely adopted (Beres et al, 2009) and the results obtained in the present study indicate that the choice of trap cultivar can have an impact on WSS preference, leading to a concentration of feeding larvae in the trap. Improvement of trap crop effectiveness is needed before this practice is widely adopted (Beres et al, 2009) and the results obtained in the present study indicate that the choice of trap cultivar can have an impact on WSS preference, leading to a concentration of feeding larvae in the trap.…”
Section: Discussionmentioning
confidence: 73%
“…Together, these biological factors inflicted higher mortality than winter conditions, and their contribution increased significantly in each successive year of the study. In 2006, ∼ 5% of stubs cut by sawflies (39 cases) had a large circular hole on the plug, suggesting predation by a beetle (Morrill et al 2001; Beres et al 2009); only one and 13 sawfly larvae were killed by this predator in 2004 and 2005, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The conclusion reached was that pith expression is suppressed in conditions of sustained days with precipitation because the amount of light a plant receives is suppressed. However, the fit of predicted vs. actual cutting was modest (R 2 = 0.55) using the model, and other attempts to use the regression model to explain variability in solid-stemmed wheat susceptibility have produced inconsistent results (Beres et al 2009). …”
Section: Introductionmentioning
confidence: 93%
“…Producers in the past have been reluctant to adopt solid-stemmed wheat as there was a perceived yield penalty when growing solid-stemmed wheat and a concern that increased wear on harvesting equipment occurs when threshing solid stems (B. Buckman, personal communication). Beres et al (2009Beres et al ( , 2007 and Nilsen et al (2016) demonstrated that solid-stemmed common and durum wheat can be agronomically superior to hollow-stemmed wheat, particularly in the presence of sawfly pressure. Lillian , the latest solid-stemmed cultivar, has occupied up to one-third of the wheat hectares in Saskatchewan and 20% of the prairie-wide wheat hectares (Anonymous 2010).…”
Section: Introductionmentioning
confidence: 99%